Growth and Development - Thirlwall, A. P (Lynne Rienner Publishers, 1995)
The purpose of the book remains the same: to introduce students to the exciting and challenging subject of developmnet economics, which draws on several branches of economics of the world's poor countries. The book combines description and analysis, with an emphasis on the elaboration of simple and useful theoretical on the elaboration of simple and useful theoritical economic models for an understanding of the issues that comprise the subject-matter of development economics.